2015
DOI: 10.1017/s1041610215000460
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional determinants of family caregiver burden in Alzheimer's disease

Abstract: It is vital to develop a service and support program with a greater emphasis on the behavioral problems and IADL deficiency of patients with AD as well as on improving the competence ability of caregivers to deal with such difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 23 publications
7
58
0
4
Order By: Relevance
“…The variable 'IADLs' showed significant negative correlations in all models, indicating that caregivers caring for persons with higher abilities (in terms of performing IADLs) experienced less burden than other caregivers. These results are consistent with those reported by Park, Sung, Kim, Kim, and Lee (2015). Furthermore, in 3 of the 4 main categories (practical care tasks, changing behaviors, and conflicts of needs), burden was negatively associated with PwD challenging behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…The variable 'IADLs' showed significant negative correlations in all models, indicating that caregivers caring for persons with higher abilities (in terms of performing IADLs) experienced less burden than other caregivers. These results are consistent with those reported by Park, Sung, Kim, Kim, and Lee (2015). Furthermore, in 3 of the 4 main categories (practical care tasks, changing behaviors, and conflicts of needs), burden was negatively associated with PwD challenging behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…personal, physical, emotional, and social) and more objective (e.g. informal caregiver time and costs) aspects of caring (Park et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…the patient's cognitive status, functional impairment, and behavioral symptoms), as well as various caregiver characteristics (e.g. their relationship to the patient and whether living with the patient or not), as being associated with the subjective caregiver burden (Beinart et al, 2012;Bergvall et al, 2011;Brodaty et al, 2014;Conde-Sala et al, 2014;Park et al, 2015). More objective but equally important burden indicators, such as caregiver time and costs, and how they change with the progression of ADD severity, have received less attention (Bergvall et al, 2011;Fisher et al, 2011;Koca et al, 2017;Wolfs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that female caregivers had a higher burden than men (Rinaldi et al, ; Pattanayak et al, ; Kim et al, ; Park et al, ), especially in the spouse group (Conde‐Sala et al, ; Reed et al, ). Other studies have reported more depressive symptoms in female caregivers associated with the burden (Wolfs et al, ; Bastawrous et al, ).…”
Section: Introductionmentioning
confidence: 99%